Perceived external prestige, affective commitment, and citizenship behaviors - Carmeli, Abraham (2005)
In a study that involved social workers in the Israeli health care system, two forms of perceived external prestige (social and economic) were identified. The results indicate that both forms of perceived external prestige augment employees' affective commitment to their organization. Compared to perceived external economic prestige, seems to have a larger effect on affective commitment. In addition, employees' affective commitment to their organization appeared to mediate the relationship between perceived external social prestige and citizenship behavior. It appears, however, that affective commitment augments altruistic behavior to a larger degree than that of compliance behavior. - Reproduced.
Keywords: Organizations; Organization behaviour